Liberalisasi Ekonomi Arab Saudi dalam Saudi Vision 2030 - Misliharira Shaumi Putri; Reni Windiani; Satwika Paramasatya (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2021)
Saudi Arabia with their conservative political life tends to create boundaries in the country. But after King Salman’s ascension to lead the country, Prince Mohammed bin Salman obtain power and authority in the country and created a plan by liberalizing the country. In Prince Mohammed bin Salman’s plan, which called Saudi Vision 2030, he has several goals that will be achieved and one of them is called a thriving economy point where the economy of Saudi Arabia can let go of their oil dependence and open opportunities for cooperation with other countries. In analysing this, the concept of economic liberalization will be used to explain Prince Mohammed bin Salman’s decision in carrying out the Saudi Vision 2030. This research is a qualitative research using data techniques through literature study. The result of this study indicates that the reason Prince Mohammed bin Salman used liberalization is to advance the economy of Saudi Arabia and also to open opportunities with other countries as an alternative to detach Saudi Arabia’s oil dependence which has not been successfully implemented in other ways. Even though it is considered to be against the principles of the country, Saudi Vision 2030 has made changes gradually and has also had a good impact on Saudi Arabia.